The Possible Role of Neuron Specific Enolase and Neurofilament Light Protein as Markers for Organophosphorus-induced Neurotoxicity - Ahmed S. El-Sayed; Ghada M. El-Galad; Mahmoud L. Sakr; Amro A. Saleh (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Acute organophosphorus (OP) poisoning is a common toxic emergency all over the worldespecially in the developing countries as Egypt. Neurological damage occurs after exposure to thesecompounds can lead to respiratory failure and death. Thus, it is important to identify the severity of poisoningand predict the need to ventilation support or death.Methods: A prospective study that included 50 adult patients presented with neurological manifestationsafter acute OP poisoning admitted to the ICU of Poison Control Center of Ain shams university (PCC-ASU),and 25 healthy volunteers. Meusering levels of Neuron Specific Enolase (NSE) and Neurofilament Light(NFL) protein and correlate this with severity according to APACHE II score and outcome of patients.Conclusion: There was a significant difference between cases and controls among levels of NSE and NFLprotein, also there was a significant correlation between NSE and NFL protein levels and prediction of bothM.V. need and mortality, so NSE and NFL protein can be used as markers for neurological damage afterexposure to OP compounds.